2014
DOI: 10.4238/2014.october.7.13
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of Aedes albopictus in Penang, Malaysia

Abstract: ABSTRACT. The mosquito Aedes albopictus is indigenous to SoutheastAsian and is a vector for arbovirus diseases. Studies examining the population genetics structure of A. albopictus have been conducted worldwide; however, there are no documented reports on the population genetic structure of A. albopictus in Malaysia, particularly in Penang. We examined the population genetics of A. albopictus based on a 445-base pair segment of the mitochondrial DNA cytochrome oxidase 1 gene among 77 individuals from 9 localit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 30 publications
3
15
0
2
Order By: Relevance
“…Our results partly support this pattern, with evidence for genetic differentiation separating northern Asia ( COI data only, no microsatellite data available), SE Asia and Indonesia (both COI and microsatellite data). Within mainland SE Asia, our data revealed little to no population structure despite high genetic diversity and COI haplotype diversity, supporting the findings of other studies [59, 69, 70]. Using climatic modelling and two mitochondrial markers, Porretta, Mastrantonio [59] suggested that the low genetic structure across this mainland SE Asian region could be explained by the demographic growth between interconnected populations of Ae .…”
Section: Discussionsupporting
confidence: 87%
“…Our results partly support this pattern, with evidence for genetic differentiation separating northern Asia ( COI data only, no microsatellite data available), SE Asia and Indonesia (both COI and microsatellite data). Within mainland SE Asia, our data revealed little to no population structure despite high genetic diversity and COI haplotype diversity, supporting the findings of other studies [59, 69, 70]. Using climatic modelling and two mitochondrial markers, Porretta, Mastrantonio [59] suggested that the low genetic structure across this mainland SE Asian region could be explained by the demographic growth between interconnected populations of Ae .…”
Section: Discussionsupporting
confidence: 87%
“…Despite the availability of mitogenomes, virtually all A. albopictus mitochondrial DNA (mtDNA) surveys were restricted to short segments of the cytochrome c oxidase subunit 1 (COI) and/or NADH dehydrogenase subunit 5 (ND5) genes, suggesting a limited phylogeographic differentiation among populations, possibly also caused by the inclusion in these studies of laboratory stocks or sibling eggs (Delatte et al, 2011; Kamgang et al, 2011, 2013; Porretta et al, 2012; Zhong et al, 2013; Zawani et al, 2014; Futami et al, 2015) and the postulated cytoplasmatic sweep caused by Wolbachia infection (Armbruster et al, 2003). However, more extensive sequencing of the COI gene has revealed more variation than previously thought (Goubert et al, 2016), a scenario also partially supported by microsatellite studies that highlighted slight genetic diversity between native and adventive populations with high variability within populations (Manni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, extensive and repeated insect control activities have involved source reduction and insecticide application, leading to the reduction and/or eradication of A. albopictus populations [68][69] . As a result, reduced levels of genetic variation were observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the main concern is that most of the genetic diversity found in the Asian tiger mosquito populations (51%) is through the use of mtDNA markers. In the last decade, the use of mtDNA has been widely used in population genetics studies for reconstructing historical patterns of population demography, admixture, biogeography and speciation in arthropods, included A. albopictus 47,69 . However, integration of mitochondrial sequences in nuclear DNA (referred to as NUMTs) has been discovered in many eukaryotes, including A. aegypti 53,[90][91][92][93] .…”
Section: Discussionmentioning
confidence: 99%